Analisis Hukum Perkara Jaminan Fidusia dalam Putusan Pengadilan Negeri Padang Nomor 38/Pdt.G/2018/PN Pdg - Ardo, Febi Kinanti (Universitas Medan Area, 2019)
The occurrence of the agreement on a vehicle financing agreement with the transfer of ownership rights fiduciary between PT. Pro Car International Finance (creditor) with a debtor No. No. 0450001897 dated May 31, 2014. The Debtor has not fulfilled its obligations since the 32nd installment due on December 31, 2016. The reason the debtor did not fulfill the obligation because the debtor has committed a crime. Upon the situation of the debtor, the PT. Pro Car International Finance states that the debtor has violated Article 1365 and Article 1366 of the Civil Code. The purpose of this study is first, to find out the form of acts against the law in Case number: 38 / Pdt.G / 2018 / PN Pdg, second, to find out the basis for judges' consideration of acts against the law in Case number: 38 / Pdt.G / 2018 / PN Pdg. This research method is normative juridical with qualitative analysis and presented descriptively. The results obtained, firstly, that the form of acts against the law in case number: 38 / Pdt.G / 2018 / PN Pdg in the form, acts that are contrary to their own legal obligations. The second result, that the basis for consideration of the Judge gave a decision on a lawsuit against the law in case number: 38 / Pdt.G / 2018 / PN Pdg is the debtor has been proven to have committed an unlawful act and the judge granted part of the demand for the Defendant to pay a loss of Rp 82,745 .681.00 with interest and penalties.